Sustainable development and growth of companies amid uncertainty in the external business environment - A. U. Kidyaeva (Путеводитель предпринимателя, 2020)
In modern conditions of instability of the external business environment, the growth of companies includes the identification of factors that affect the development of the company and its stability. In scientific decision sources, there are different approaches to assessing the growth of companies, key indicators and management decisions. The article contains some aspects of the study of this problem.